Prediction of complications in a high-risk cohort of patients undergoing corrective arthrodesis of late stage Charcot deformity based on the PEDIS score. Issue 1 (December 2015) - Eschler, Anica; Gradl, Georg; Wussow, Annekatrin; Mittlmeier, Thomas
Abstract Background All diabetic neuroosteoarthropathy (Charcot arthropathy) treatment concepts are focused on a long-term infection-free, ulcer-free, and plantigrade sufficiently stable foot in order to avoid amputation. Reconstructive arthrodesis techniques for severe deformities are associated with high postoperative complication rates. This study reports a detailed complication analysis and provides a strategy that may help detect patients at risk for a complicated postoperative course. Methods The study comprised 43 feet in 37 patients with severe non-plantigrade or unstable Charcot deformity, Eichenholtz stages II/III (Sanders and Frykberg types II-V), who underwent reconstructive arthrodesis of the mid- and/or hindfoot. Patients were retrospectively enrolled 4.5 years postoperatively (range 1.8–11.2 years). All patients showed at least two out of five positive Pinzur high-risk criteria (immuno-compromising illnesses, large bone deformity, longstanding ulcer overlying infected bone, regional osteopenia, obesity). Follow-up included a detailed clinical analysis and radiologic assessment with emphasis on complication analysis and evaluation in accordance to the PEDIS classification system. Results Significantly lower overall complication rates, as well as re-operation, reulceration and amputation counts were found for patients with a cumulative PEDIS count below 7. For PEDIS single criteria, significantly lower overall complication rates were found for patients without signs of occlusive peripheral artery disease, an ulcer extent <0.9 cm2, ulcer depth including erosion and inflammation of the skin and subcutaneous tissues only. Soft-tissue complications affected 49 % of patients, hardware breakage 33 %, hardware loosening 19 %, non-union 18 % and amputation 21 %. Radiographs revealed a correct reconstruction and restoration of all foot axes postoperatively with partial recollapse at the lateral foot column; however, fixation strength for the medial column was maintained. Conclusions Internal corrective arthrodesis for patients within the deformed stages of Charcot deformity can provide adequate reconstruction, as assessed by intraoperative radiographic measures, that exhibit superior long-term stability for the medial column. Despite a high risk patient population, a favourable outcome in terms of overall complication, re-ulceration, and amputation rates for patients/feet with a cumulative PEDIS count below 7 was found. The cut-off value of 7 may aid clinical decision-making during preoperative planning for Charcot deformity.